EFFECTS OF THE USE OF MOBILE PHONE APPLICATION ON HIGHER INSTITUTIONS PHYSICS STUDENTS’ ACADEMIC ACHIEVEMENT IN EKITI STATE, NIGERIA. - R.O., ASUBIOJO,; E.E, UKOH,; A.L., ALADEJANA, (IJRDO- Journal of Educational Research, 2019)
The study investigated the effect of use of mobile phone application on Higher Institutions’ Physics Students Academic Achievement in Ekiti State, Nigeria. Three hypotheses were used for the study. A pretest-posttest quasi-experimental design was adopted for the study.  The sample of the study consists of eighty students from four tertiary institutions in Ekiti state. The research instruments for the study were Physics mobile phone application & self-structured achievement test to collect data. Data collected were analysed using t-test statistical tool. One of the findings of the study revealed that there was significant in the physics students’ academic achievement The study concluded that Students taught using mobile phone application activity performed better than their counterparts, taught without mobile phone application. Therefore, it was recommended that Physics lecturer should be trained on how best to involve students to use mobile phone application during physics lecture so as to facilitate students’ academic achievement.